2018
DOI: 10.3233/jad-171108
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Aluminum and Iron in Nuclei of Nerve Cells in Brains of Patients with Alzheimer’s Disease

Abstract: Increasing evidence indicates that metal-induced oxidative stress plays a pivotal role in the pathogenesis of Alzheimer’s disease (AD). Recently, the presence of 8-hydroxydeoxyguanosine, a biomarker of oxidative DNA damage, was demonstrated in nuclear DNA (nDNA) in the AD brain. Iron (Fe) is a pro-oxidant metal capable of generating hydroxyl radicals that can oxidize DNA, and aluminum (Al) has been reported to facilitate Fe-mediated oxidation. In the present study, we examined the elements contained in the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 127 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Alzheimer's disease (AD) is the leading cause of dementia worldwide, and AD patients and their families urgently require novel therapeutics to prevent and slow the progression of this devastating disorder. Hallmarks of AD include amyloid-␤ (A␤) peptide secretion and deposition into neuritic plaques, tau protein hyperphosphorylation and neurofibrillary tangle formation, metal ion dyshomeostasis [1][2][3][4][5][6][7][8][9], oxidative stress and lipid, nucleic acid, and protein damage [10][11][12][13], abortive cell cycle reentry [14][15][16][17][18][19][20][21][22][23][24][25][26], neuroinflammation and microbial dysbiosis [27][28][29][30][31][32][33], insulin resistance [34,35], cerebrovascular dysfunction [36][37][38], synaptic dysfunction [39,40], neuronal loss, endoplasmic reticulum stress [41][42][43][44], and mitochondrial dysfunction [...…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the leading cause of dementia worldwide, and AD patients and their families urgently require novel therapeutics to prevent and slow the progression of this devastating disorder. Hallmarks of AD include amyloid-␤ (A␤) peptide secretion and deposition into neuritic plaques, tau protein hyperphosphorylation and neurofibrillary tangle formation, metal ion dyshomeostasis [1][2][3][4][5][6][7][8][9], oxidative stress and lipid, nucleic acid, and protein damage [10][11][12][13], abortive cell cycle reentry [14][15][16][17][18][19][20][21][22][23][24][25][26], neuroinflammation and microbial dysbiosis [27][28][29][30][31][32][33], insulin resistance [34,35], cerebrovascular dysfunction [36][37][38], synaptic dysfunction [39,40], neuronal loss, endoplasmic reticulum stress [41][42][43][44], and mitochondrial dysfunction [...…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that aluminum could increase the levels of reactive oxygen species in the brain tissue ( Bali et al, 2019 ; Simunkova et al, 2019 ). Based on the results obtained from ICP and higher concentrations of aluminum ions, this ion crosses BBB and enters the brain tissue, while in neurons, aluminum participates in the Fenton reaction in which iron is oxidized and induces oxidative stress ( Mujika et al, 2014 ; Yumoto et al, 2018 ). Currently, aluminum has been reported as an inducer of oxidative stress leading to the appearance of AD markers, so that it has been used to develop rat models of AD ( Almuhayawi et al, 2020 ; Ogunlade et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolar compartment of nigral neurons, even in non-diseased conditions, displayed clear evidence for the abundant presence of P, S, Ca, but also of Zn and Fe. The presence of Fe in the nucleoli has so far been imaged by XRF in plants 47 and mammalian cells 48 , and by other techniques in aged or diseased brains 49 , 50 . Fe levels in nucleoli of dopaminergic neurons were quantified in the present work (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%